Australian black beetle expansion through Christchurch city highlights a risk to pastoral agriculture on the Canterbury plains - Townsend, R.J.; McNeill, M.R.; Jackson, T.A. (New Zealand Plant Protection, 2008)
The Australian black beetle Adoryphorus couloni (also known as the redheaded cockchafer) was found in large numbers in Barrington Park in Christchurch in May 2008 Severely damaged areas comprised 1020 of the park with populations reaching over 300 larvae/m2 The thatch layer produced on sports fields appears ideal for this insect which favours grasslands with high organic matter levels and could explain the very high grub numbers To reach a population of this size A couloni had probably colonised and remained undetected in the park for several years In Australia the insect is a serious pest of pastures Severe damage occurred in Tasmania in the 1980s and 1990s when the insect spread through the central Midlands stripping bare thousands of hectares of pasture The beetle was accidentally introduced to Canterbury through Lyttelton harbour in the 1960s and has slowly spread around the Port Hills in lowquality hill pastures The outbreak in Christchurch marks the first move of this pest into habitat favourable for development of populations large enough to pose a serious risk of further westward expansion onto the Canterbury plains AgResearch is assisting the Christchurch City Council with identification and control recommendations for the pest and is evaluating potential biocontrol measures